Improving the culture of safety among healthcare workers: Integration of different instruments to gain major insights and drive effective changes. (13th October 2021) - Tocco Tussardi, Ilaria; Moretti, Francesca; Capasso, Mario; Niero, Valentina; Visentin, Donatella; Dalla Barba, Livio; Tardivo, Stefano
Abstract: The Safety Attitude Questionnaire (SAQ) and Manchester Patient Safety Framework (MaPSaF) are known as effective tools to assess patient safety culture and climate and develop targeted strategies. However, they are seldom applied in an integrated way. The aim of this study was to conduct an implementation project through a novel use of both instruments to gain unique insights. The Italian version of MaPSaF and SAQ were administered to 1, 759 healthcare workers from three Italian hospitals (response rate: MaPSaF 70.5%, SAQ 61.6%). MaPSaF evaluation proved an overall bureaucratic level of patient safety culture. SAQ scores showed a predominance of neutral scores (75.99%). The dimension perception of management gained the lowest mean score (53.32), while Stress recognition obtained the highest (75.17). Safety climate perception differed significantly among groups: working in a small hospital, in a medical department, and being a physician were associated with the most positive results. The majority (67.1%) of responders to both MaPSaF and SAQ considered the two instruments as providing with different and complementary information. Overall, results showed that an integrated approach in the evaluation of an organisation's safety culture may result useful for an in‐depth analysis of the criticalities and the adoption of appropriate improvement strategies.